UPAYA LEGITIMASI SYARIâ€™AT ISLAM DALAM HUKUM NASIONAL (Dialektika Sejarah UUD 1945 dan Piagam Jakarta) - Pancasilawati, Abnan (Mazahib, 2007)
This article is to discuss the role of Islamic law in Indonesia. In particular, it will analyze the history of Jakarta Charter during the process of 1945 Constitution drafting. Jakarta Charter was a proposal from the subcommittee of the Investigating Committee for the Preparation of Indonesian Independence (BPUPKI) to resolve the controversies around Islamâ€™s role in the state in 1945. Â It proposed to add several additional words to the first principle of Pancasila â€œBelief in God,â€ namely â€œwith the obligation for adherents of Islam to carry out Islamic law.â€ Â This addition made reference to the enforcement of Islamic law in Indonesia. Â The Jakarta Charter was intended to serve as the preamble of the 1945 Indonesian Constitution. Â Yet, since it comprised the crucial phrase the concept of unity of newly established Indonesia, which is very pluralistic in nature, the Jakarta Charter was dropped from the preamble of the Constitution in 1945.